A modern approach to biofilm-related orthopaedic implant infections : Advances in microbiology, infectious diseases and public health. Volume 5 - Drago, Lorenzo (Springer, 2017)
"This book discusses Prosthetic Joint Infection (PJI), which remains one of the most common problems necessitating revision arthroplasty. It pursues a multidisciplinary approach, bringing together opinions from the leading experts in the field. The book identifies the potential causes of these infections, provides sound diagnostic criteria guidelines, and explains how these prosthetic infections are managed from orthopedic surgery, clinical and diagnostic perspectives. PJI can lead to multiple revision surgeries and significant patient morbidity. Periprosthetic infection rates remain around 1-2% after primary total hip and knee arthroplasty and account for approximately 7-12% of all revision cases. Orthopedic hardware infections are much-feared and costly complications that can occur when these devices are implemented both in traumatic cases as well as in joint replacement surgery. Because these infections can lead to higher morbidity, it is important to understand their pathophysiology and the principles behind their diagnosis and initial treatment. The pathogenesis of these kinds of infections is intimately connected to the biofilm-producing trait characteristic of many microorganisms, which can have a critical effect on the likely success of treatments. The book offers a unique guide for all scientists working in arthroplasty who are seeking an update on the field, and for newcomers alike"--Publisher's description.
Keywords: Implants, Artificial -- Complications.; Biofilms.; elektronické knihy; electronic books